2011
DOI: 10.4103/0970-9371.83472
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology of a case of micropapillary variant of urothelial carcinoma of bladder

Abstract: Neoplastic urothelium has the capacity to demonstrate enormous plasticity. A variety of unusual morphological variants of urothelial carcinoma have been described. Micropapillary variant of urothelial carcinoma is a rare and recently described bladder tumor, associated with poor prognosis. We present the cytological features of micropapillary urothelial carcinoma in a 65-year-old man with bladder mass. The cytological features include tightly cohesive clusters of micropapillary component admixed with urothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
1
2
1
Order By: Relevance
“…However, if the background is extensively necrotic, the possibility of MPUC can be low in urine cytology specimens. In previous reports, most MPUC cases showed a high N/C ratio 5-10. However, in our study, we found that the N/C ratio of MPUC was moderate to high-the same as that of HGUC.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…However, if the background is extensively necrotic, the possibility of MPUC can be low in urine cytology specimens. In previous reports, most MPUC cases showed a high N/C ratio 5-10. However, in our study, we found that the N/C ratio of MPUC was moderate to high-the same as that of HGUC.…”
Section: Discussioncontrasting
confidence: 71%
“…According to the previous reports, the most characteristic cytologic finding of this study was prominent small and tight cellular clusters 5-10. The morphology of the clusters was variable, showing spheroid patterns, three-dimensional cell balls, rosette-like clusters and micropapillary patterns without fibrovascular cores.…”
Section: Discussionsupporting
confidence: 67%
“…The cytology of this MPC variant is basically a mixture of a high-grade urothelial carcinoma with partial architectural features of a low-grade neoplasm [9]. Previous cytologic reports include two series and a few case reports, some of which involve FNA [9,10,11,12,13,14,15,16]. The present study is generally in agreement with these previous papers, which report a predominance of smears, showing atypical cells distributed mainly as tight clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Cytologic reports describing features of the micropapillary variant of transitional cell carcinoma are still scarce [9,10,11,12,13,14,15,16]. The two published series show some differences probably related to different methods employed in the selection, collection and processing of the specimens [14,16].…”
Section: Introductionmentioning
confidence: 99%